CFD Simulation Study on Airflow Dynamics Around a Cricket Ball: Effects of Velocity and Surface Modifications on Aerodynamic Performance - Catur Harsito; Enock Michael Kandimba; Raihan Danu Ramanda; Putra Adil Wicaksana; Yuki Trisnoaji; Singgih Dwi Prasetyo (Mekanika: Majalah Ilmiah Mekanika, 2026)
This study investigates the aerodynamic behavior of a cricket ball at various velocities using Computational Fluid Dynamics (CFD) in ANSYS Fluent, focusing on the effects of speed and surface modifications on aerodynamic forces and pressure distribution. The cricket ball geometry was simplified by replacing the seam with a protruding flat surface. Simulations were performed at airflow velocities of 20, 30, and 40 m/s using the realizable k-ε turbulence model, with air properties set to a density of 1.225 kg/m³ and dynamic viscosity of 1.81×10-⁵ Pa-s. At 20 m/s, the inlet and outlet mass flow rates were 50.306891 kg/s and -50.306901 kg/s, with a net imbalance of        -9.3×10-⁶ kg/s, generating a drag force of 0.5 N, a lift force of 0.2 N, and a pressure difference of 50 Pa. At 30 m/s, the inlet and outlet rates were 75.460373 kg/s and -75.464958 kg/s, respectively, resulting in a net imbalance of -0.004585 kg/s. The flow was fully turbulent, producing a drag force of 3.5 N, a lift force of 1.5 N, and a pressure difference of 250 Pa. Increasing velocity boosts drag, lift, and pressure differences. At the same time, the flat surface enhances asymmetry, vortices, and swing at higher speeds.